ELECTRON-STIMULATED DESORPTION OF LITHIUM ATOMS FROM OXYGEN MONOLAYER COVERED TUNGSTEN - Yu.A. Kuznetsov; M.N. Lapushkin (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2019)
The electron-stimulated desorption of neutral lithium atoms from the oxygen monolayer covered the tungsten surface have been studied. The model of the atom electron-stimulated desorption processes on the tungsten surface with the adsorbed oxygen monolayer have been suggested. Both common and different features of the electron-stimulated desorption processes have been foundfor high-energy and low-energy peaks in the kinetic energy distributions of the desorbed atoms.